Misoprostol Intoxication in the Third Trimester in Pregnant Patients - Guerrero, Christian Camilo Galíndez; Cervantes, Israel David Echavez; Ayala, Gabriela Carolina Alvear; Marín, Lina Paola Vélez; Cuello, Dalila Rosa Fernández; Chuy, Adriana Inés Rodríguez; Ustariz, Daniel Ramirez; Conde, Sebastian Durango (Jour Med Resh and Health Sci, 2022)
Background: Misoprostol is an analog of Prostaglandin (PG) E1, which initially began to be marketed in pharmacies in many places since the end of the 1980s under the trade name of Cytotec. Methodology: A bibliographic review was carried out through various databases from 2012 to 2021; The search and selection of articles was carried out in journals indexed in English and Spanish. The following keywords were used: intoxication, misoprostol, pregnant patients. Results: Exposure to misoprostol has been associated with a number of defects including arthrogryposis and limb reduction, brain anomalies, gastroschisis, and Moebius syndrome. Conclusion: For the gynecological, misoprostol is a very useful drug for the interruption of pregnancy at any stage of this, not only for this, it also helps to expel a missed abortion, it is effective for the induction of labor, and it also acts as a treatment for postpartum hemorrhage.